Plants, soil properties and microbes directly and positively drive ecosystem multifunctionality in a plantation chronosequence. (22nd July 2022) - Wang, Jianqing; Shi, Xiuzhen; Lucas‐Borja, Manuel Esteban; Lam, Shu Kee; Wang, Zhenyu; Huang, Zhiqun
Abstract: Chinese fir ( Cunninghamia lanceolata ) is the main plantation species in the subtropical region of China. However, the shift in ecosystem multifunctionality with stand development remains largely unexplored for these plantations. This study used a chronosequence to investigate the variations of ecosystem multifunctionality by employing individual functions and identified its driving factors in Chinese fir plantations. The findings provide strong evidence that the individual functions of carbon stocks, water regulation and wood production increased with stand ages, but the tradeoff of individual functions did not significantly increase ecosystem multifunctionality. Soil microbial parameters (the abundances of bacteria, fungi and actinomycete), soil properties (soil moisture, total carbon and total nitrogen), and plant parameters (the shrub layer cover and total understory cover) exhibited positive correlations with ecosystem multifunctionality. The structural equation model revealed that plants, soil properties and microbes pathways explained 83% of the total variance in ecosystem multifunctionality. Results showed that plants, soil microbes and properties directly and significantly affected ecosystem multifunctionality with path coefficients of 0.404, 0.487 and 0.334, respectively. Soil microbes were identified as the top direct predictor for ecosystem multifunctionality, while plant and soil properties had strong direct and positive effects on ecosystem multifunctionality. These results verified that soil microbes, plants and soil properties directly and positively regulated ecosystem multifunctionality. Our findings demonstrate that ecosystem multifunctionality should be considered as a comprehensive ecological indicator for ecosystem services and functions, and sustainable plantation management. This study highlights the importance of conserving soil microbes for maintaining multifunctionality in Chinese fir plantations.